ANALISIS AKAD TIJARAH PADA TRANSAKSI FINTECH SYARIAH DENGAN PENDEKATAN MAQHASID - Dodi Yarli (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2018)
Financial technology is an activity that focuses on providingfinancial services ideas using software. Which is fintech, it expectedthat various facilities can be obtained later. The development of fintechbegan since the discovery of blockhain and cryptocurrency. In addition,this development is also one of the developments in digital-basedtechnology and is a new innovation and his impact on all economicactivities, especially in the Islamic economy. As for Fintech Syariah, of course it must be based on an Islamicperspective and refer to Maqashid Syari'ah al-Khams and containbenefits for every transaction carried out by the contractor.  All formsof economy and business transactions originating from the Qur'an andthe Sunnah are clear,  paying attention to and protecting the rights ofeach individual in order to uphold justice and eliminate injustice intransacting through the shariah fintech.